2013
DOI: 10.1007/s00464-013-3126-x
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of risk factors for surgical site infection after laparoscopic colorectal surgery

Abstract: Alterations in surgical technique and specimen extraction site can reduce wound-related complications after laparoscopic colorectal resections. Remaining risk factors are largely nonmodifiable from a surgeon's perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 23 publications
2
30
0
3
Order By: Relevance
“…In patients with mild or moderate hypertension, drugs used in chronic treatment may increase the need for active management of hypertensive episodes. Drosdeck et al24 reports that diabetes is a significant risk factor for incisional hernias. In contrast, no association between hypertension, diabetes, and postoperative morbidity early bowel obstruction is observed in another study 25.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with mild or moderate hypertension, drugs used in chronic treatment may increase the need for active management of hypertensive episodes. Drosdeck et al24 reports that diabetes is a significant risk factor for incisional hernias. In contrast, no association between hypertension, diabetes, and postoperative morbidity early bowel obstruction is observed in another study 25.…”
Section: Discussionmentioning
confidence: 99%
“…5 several small studies have shown a trend toward increased rates of ssi in iBD patients in relation to surgical approach, wound classification, and immunosuppressive state. [5][6][7][8][9] however, no multi-institutional study looking solely at the relationship between iBD and ssi has validated these findings.…”
mentioning
confidence: 81%
“…Nonetheless, infection following operation remains a major factor affecting the morbidity of the patients, and surgical site infection (SSI) is particularly common following colorectal procedures, with reported rates ranging from 5-26 % [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%